2019
DOI: 10.3389/fimmu.2019.00717
|View full text |Cite
|
Sign up to set email alerts
|

Envelope-Specific Recognition Patterns of HIV Vaccine-Induced IgG Antibodies Are Linked to Immunogen Structure and Sequence

Abstract: Background: A better understanding of the parameters influencing vaccine-induced IgG recognition of individual antigenic regions and their variants within the HIV Envelope protein (Env) can help to improve design of preventive HIV vaccines. Methods: Env-specific IgG responses were mapped in samples of the UKHVC003 Standard Group (UK003SG, n = 11 from UK) and TaMoVac01 (TMV01, n = 17 from Tanzania) HIV vaccine trials. Both trials c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 33 publications
9
17
0
Order By: Relevance
“…IgG antibodies to the HIV-1 Env variable (V) regions V1 and V2, as well as V3, were found to correlate with a reduced risk of HIV-1 infection, while the presence of IgA Env-binding antibodies was associated with an increased risk of infection (9,10). Antibody responses to other linear epitopes of the HIV-1 Env gp120 did not correlate with infection risk (10), which might be due to the fact that many of these regions are not accessible on a native HIV-1 Env trimer (11). Viral sieve analyses showed that the RV144 vaccine regimen induced selection of viral variants with point mutations in the V2 and V3 regions, indicating that strain-specific V2 and V3 antibodies drove viral mutation to escape the vaccine-induced immune response against HIV-1 (12,13).…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…IgG antibodies to the HIV-1 Env variable (V) regions V1 and V2, as well as V3, were found to correlate with a reduced risk of HIV-1 infection, while the presence of IgA Env-binding antibodies was associated with an increased risk of infection (9,10). Antibody responses to other linear epitopes of the HIV-1 Env gp120 did not correlate with infection risk (10), which might be due to the fact that many of these regions are not accessible on a native HIV-1 Env trimer (11). Viral sieve analyses showed that the RV144 vaccine regimen induced selection of viral variants with point mutations in the V2 and V3 regions, indicating that strain-specific V2 and V3 antibodies drove viral mutation to escape the vaccine-induced immune response against HIV-1 (12,13).…”
Section: Introductionmentioning
confidence: 95%
“…The peptide array design has been previously described in detail by our group (11). In brief, gp120 and gp41 sequences of 8 recently transmitted HIV primary isolates of different subtypes (A, B, C, CRF01_AE and CRF02_AG) were selected for inclusion in the peptide array design to represent the HIV Env variants of the current global pandemic.…”
Section: Peptide Array Mapping Of the Hiv Env-specific Igg Antibody Rmentioning
confidence: 99%
See 3 more Smart Citations